Improving Black Entrepreneurship through Cannabis-Related Education - Alicia E. Reid; Micah E. S. Crump; Robert P. Singh (MDPI AG, 2024)
Economic inequality is a significant and growing issue in the U.S., particularly within Black communities. Improving Black entrepreneurship is critical to addressing the economic gaps. In this paper, we discuss a unique, newly established educational program focused on cannabis education at Medgar Evers College (MEC) in New York. One of the goals of the new program is to increase Black entrepreneurship in the rapidly growing cannabis industry. For decades, cannabis use and distribution were criminal offenses that led to the disproportionate incarceration of Black individuals compared to White individuals. As it is being decriminalized across the country, and medical and recreational use spreads, the tool formerly used for Black incarceration can now become a tool for advancing Black entrepreneurship. To work and/or operate a venture in the cannabis industry requires students to understand a range of issues and build a strong foundation of broad knowledge. We discuss the emerging curricula and illustrate some of the elements that will help spur successful new venture creation led by Black and minority entrepreneurs in this exciting new field. Some early successes and lessons learned are discussed, which can help other educational institutions looking to create or improve their own cannabis-related curricula.